TUMPANG PUASA DAN HAJI PULO IE (Studi Tentang Polemik Dalam Persepsi Masyarakat di Meulaboh Aceh Barat) - Triyanto Triyanto (Jurnal Community, 2018)
In the life of the Islamic community, you can be sure to know, experience and do Ramadan fasting, which must be done for a full month. On a normal day, it is not easy to fast someone, because there are many temptations to preserve thirst, hunger and emotions. If a day is overwhelmed, how can it take a month? Again, it really is not easy to get it right. If Muslims can afford to travel to Mecca, which is located in Saudi Arabia, the number is estimated at 6218 km. A long distance for an Acehnese trip. Long ago our ancestors made hajj with months of sea voyages and were full of risks. Even now, the hajj is not easy, because it has to raise enough funds for strength and health. But what if the Tumpang fasting is done just at the beginning and end of Ramadhan? What if Muslims do not have enough money to go on a hajj to Mecca, and it turns out they can do it in a village called Pulo Ie? Of course, there will be many Islamic organizations and Islamic leaders, including ulama, who claim to be bid'ah! The purpose of this article is to investigate how the actual Tumpang fasting and to make a hajj to Pulo Ie at Seunagan, Nagan Raya Aceh. Keywords: Hajj, Fasting, Tumpang, Abu Habib Muda, Seunagan, Nagan Raya